Thematic Review of Master’s Theses of Iranian Students on Relationship between Russian and Persian Literatures - A. Golkar; M. R. Mohammadi; Z. Sadeghi Sahlabad (Научный диалог)
The review of master’s theses defended in the period of 2006-2016 at the Department of Russian language of Tehran University in the field of literary relations between Iran and Russia is made. The authors highlight the main perspectives of comparative studies of Iranian undergraduates who studies Russian, identify the main features of the process of mutual influences of Persian and Russian literature. It is shown which Russian and Persian writers, periods in history of literature and scientific approaches are most popular in the academic and educational environment of Iran. The article also reveals a number of thematic areas that remain outside the field of view of undergraduates, although their scientific development seems very promising. Special attention is paid to research methodology. The conclusion is made that in Iran the themes in which influence of East, Islamic world on creativity of the Russian writers is revealed are deeply studied. Comparison of Russian and Iranian folklore is carried out. It is noted that among the “white spots” of scientific research in Iranian literature there is the study of modern Russian literature, coverage of the role of Persian translations of works of Russian writers and their reception in Iran, as well as generalizing research of a theoretical nature.